PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN STUDI EMPIRIS PADA PERBANKAN DI BURSA EFEK INDONESIA PERIODE 2014-2016 - Ranu, Fristianty Sumarliana; Frisdiantara, Christea; Mustikowati, Rita Indah (Jurnal Riset Mahasiswa Akuntansi, 2017)
This study aims to determine (1) Influence of the Independent Board of Commissioners on the Financial Performance of Banks registered on the Indonesia Stock Exchange in the 2014-2016 period, (2) Influence of the Board of Directors on the Financial Performance of Banks listed on the Indonesia Stock Exchange in the 2014-2016 period, (3) Influence of the Audit Committee on the Financial Performance of Banks registered on the IDX for the 2014-2016 period, (4) Effect of Company Size on the Financial Performance of the banks registered on the IDX for the 2014-2016 period and (5) Influence of the Independent Board of Commissioners, the Board of Directors, the Audit Committee, and the Size of the Company Banking Financial Performance registered on the Indonesia Stock Exchange for the 2014-2016 period. The population is all banks listed on the Indonesia Stock Exchange in the 2014-2016 period, amounting to 43 banks. Sample selection through purposive sampling method. Data analysis techniques used are descriptive statistics, multiple linear regression test, classic assumption test, hypothesis test and coefficient of determination (r2)